Access to care among Medicaid and uninsured patients in community health centers after the Affordable Care Act - Veri Seo; Travis P. Baggett; Anne N. Thorndike; Peter Hull; John Hsu; Joseph P. Newhouse; Vicki Fung (BMC, 2019)
Abstract Background The Affordable Care Act expanded Medicaid and increased federal funding for Community Health Centers (CHCs). To examine the role of Medicaid coverage on care patterns for those with available safety net care, we assessed differences in access to care for CHC patients with continuous Medicaid coverage vs. gaps in insurance coverage in the last year. Methods We used data on adult respondents from the 2014 Health Center Patient Survey (N = 1720) with continuous Medicaid coverage vs. those with some period without insurance coverage in the last 12 months. We examined reported need for any medical care, mental health care, prescription drugs, dental care, and referrals for care outside of the CHC in the last 12 months, and reports of being delayed or unable to get needed care by insurance status. We used logistic regression to assess the association between insurance status and care access, adjusting for patient characteristics. Results Patients with insurance gaps and continuous Medicaid coverage reported similar levels of need for most types of care in the last 12 months, but those with insurance gaps were significantly more likely to report having difficulty obtaining medical care, prescription drugs, dental care, and completing outside referrals. Of those with incomplete referrals for care outside of the CHC, patients with insurance gaps were more likely than those with continuous Medicaid to cite cost or insurance-related reasons for not following up (70% vs. 19%, p < 0.01). Conclusions Having continuous Medicaid coverage appeared to mitigate barriers to care for CHC patients compared to having intermittent or no insurance coverage over the last year. Policies that increase disruptions in Medicaid coverage could adversely impact access to care, even among those with available safety net care.